Anatomical and morphometric evaluation of the third trochanter in dry femurs (Annals of Medical Research, 2024)
Aim: The objective of the study is to fill the gaps in knowledge about the third trochanter (TT)  by quantifying these anatomical measurements and examining the morphological characteristics associated with its presence.Materials and Methods: The length, diameter, types, location, and distances to the greater and lesser trochanters of the third trochanter were determined. Measurements of the greater trochanter, lesser trochanter, and gluteal tubercle lengths and diameters of 144 femurs available in the Medical Faculty laboratory were taken using a digital caliper to calculate their relationships with the third trochanter (TT).Results: In our study of 144 dry femurs, we identified the presence of TTs in 25.35% of cases, which equates to 36 femurs. Notably, we observed significant gender differences in the prevalence of TTs, with 27 males having TTs compared to 9 females, indicating a higher occurrence of TTs in males (p= 0.027). Average femur length and width were 41.23 mm and 27.05 mm, Greater trochanter had dimensions of 45.27 mm by 38.66 mm, and lesser trochanter measured 24.89 mm by 17.78 mm. In TT-identified femurs, the TT had an average length and diameter of 39.46 mm and 26.01 mm, respectively. The study also provided measurements for gluteal tuberosity and trochanter distances, helping in orthopedic and anatomical research.Conclusion: In our study conducted on 144 dry femurs with sex determination using morphometric methods, it was found that the third trochanter (TT) was detected in 25.35% of the cases, showing significant sexual dimorphism in favor of males. These femurs exhibited specific morphological characteristics, including an increased superior sagittal diameter, elevated diaphysis platymetry index, and an enlarged greater trochanter. Additionally, the presence of the third trochanter may reflect adaptations to mechanical forces and evolutionary changes, making it a valuable trait for anatomical and genomic studies, as well as surgical procedures that require access to the femoral medullary cavity.
Keywords: Third trochanter; Trochanter tertius; Femur; Gluteal tuberosity